2019
DOI: 10.1039/c9nr01255a
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-primed exosomes potently ameliorate cognitive function in AD mice by inhibiting hyperphosphorylation of the Tau protein through the AKT/GSK-3β pathway

Abstract: Curcumin-primed exosomes (Exo-Cur) can better relieve the symptoms of AD by inhibiting phosphorylation of Tau protein through AKT/GSK-3β pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(174 citation statements)
references
References 45 publications
1
172
0
1
Order By: Relevance
“…Curcumin encapsulated in exosomes crosses the BBB and reaches the neuronal tissue where it inhibits the hyperphosphorylation of Tau proteins, thus reducing the symptoms of Alzheimer's disease. This mechanism is explained by the activation of the AKT/GSK-3β pathway [143].…”
Section: Nanoformulation: Molecules Extraction Techniques and Alzheimentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin encapsulated in exosomes crosses the BBB and reaches the neuronal tissue where it inhibits the hyperphosphorylation of Tau proteins, thus reducing the symptoms of Alzheimer's disease. This mechanism is explained by the activation of the AKT/GSK-3β pathway [143].…”
Section: Nanoformulation: Molecules Extraction Techniques and Alzheimentioning
confidence: 99%
“…hyperphosphorylation of Tau proteins, thus reducing the symptoms of Alzheimer's disease. This mechanism is explained by the activation of the AKT/GSK-3β pathway [143]. Magnetic CUR nanoparticles can be used in neurodegenerative disorders under the influence of external magnetic fields [144].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…[ 25 ] For example, one report illustrated that exosomes loaded with curcumin effectively improved cognitive function in C57BL/6 mice inducing AD model in vivo. [ 26 ] In another study, Xue and his colleagues used neutrophils as carrier, which showed significant improvement in BBB‐traversing ability. [ 27 ] Receptor‐mediated transcytosis (RMT) is the most commonly used strategy to enable chemotherapeutics to cross the BBB.…”
Section: Nps For Drug Delivery Into the Brain: Role And Advantagesmentioning
confidence: 99%
“…Recently, neuroinflammation induced by proinflammatory cytokines was suggested as a novel pathogenesis of ASD, particularly in irritability and socialization problems [275]. As a therapeutic approach, stem-cell-derived exosomes containing anti-inflammatory molecules could be used as efficient carriers for delivering anti-inflammatory molecules across the blood-brain barrier [276]. These attempts have already been made to alleviate the symptoms of Alzheimer's disease [276].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…As a therapeutic approach, stem-cell-derived exosomes containing anti-inflammatory molecules could be used as efficient carriers for delivering anti-inflammatory molecules across the blood-brain barrier [276]. These attempts have already been made to alleviate the symptoms of Alzheimer's disease [276].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%